The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/irv.13066
|View full text |Cite
|
Sign up to set email alerts
|

Burden and severity of children's hospitalizations by respiratory syncytial virus in Portugal, 2015–2018

Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory infection (ALRI) in young children and is of considerable burden on healthcare systems. Our study aimed to evaluate ALRI hospitalizations related to RSV in children in Portugal. Methods:We reviewed hospitalizations potentially related to RSV in children aged <5 years from 2015 to 2018, using anonymized administrative data covering all public hospital discharges in mainland Portugal. Three case definitions were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
4
7
0
Order By: Relevance
“…22 However, the majority of infants hospitalized with RSV were born at term and were previously healthy, similar to findings from other studies. [23][24][25] While it is important to identify infants at greatest risk of severe RSV infection in order to determine those who could benefit most from interventions aiming to either prevent infection or reduce disease severity, prevention strategies targeting only highrisk infants will have a limited effect at the population level, in particular on the total burden of RSV infection. 23 Results from the bronchiolitis-coded, RTI-coded and RSV-predicted cohorts corroborate the results from the RSV-coded cohort.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…22 However, the majority of infants hospitalized with RSV were born at term and were previously healthy, similar to findings from other studies. [23][24][25] While it is important to identify infants at greatest risk of severe RSV infection in order to determine those who could benefit most from interventions aiming to either prevent infection or reduce disease severity, prevention strategies targeting only highrisk infants will have a limited effect at the population level, in particular on the total burden of RSV infection. 23 Results from the bronchiolitis-coded, RTI-coded and RSV-predicted cohorts corroborate the results from the RSV-coded cohort.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…In a recent study of RSV in Portugal [9], it is shown that RSV is accountable for a substantial number of hospitalizations in children, especially when they have less than one year old. Hospitalizations are mainly motivated by healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalizations are mainly motivated by healthy children. The authors of [9] conclude their study claiming that the creation of a universal RSV surveillance system to guide prevention strategies are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is particularly severe in children under 6 months, resulting in 6.6 million infections per year and 1.4 million hospital admissions [1]. Nonetheless, most hospitalizations occur in children under 3 months of age [2,3].…”
Section: Introductionmentioning
confidence: 99%